Simple Visualization of Universal Ferroelastic Domain Walls in Lead Halide Perovskites. Issue 8 (20th December 2022) - Zhang, Bo; Sun, Shuo; Jia, Yinglu; Dai, Jun; Rathnayake, Dhanusha T.N.; Huang, Xi; Casasent, Jade; Adhikari, Gopi; Billy, Temban Acha; Lu, Yongfeng; Zeng, Xiao Cheng; Guo, Yinsheng
Abstract: Domain features and domain walls in lead halide perovskites (LHPs) have attracted broad interest due to their potential impact on optoelectronic properties of this unique class of solution‐processable semiconductors. Using nonpolarized light and simple imaging configurations, ferroelastic twin domains and their switchings through multiple consecutive phase transitions are directly visualized. This direct optical contrast originates from finite optical reflections at the wall interface between two compositionally identical, orientationally different, optically anisotropic domains inside the material bulk. The findings show these domain walls serve as internal reflectors and steer energy transport inside halide perovskites optically . First‐principles calculations show universal low domain‐wall energies and modest energy barriers of domain switching, confirming their prevalent appearance, stable presence, and facile moving observed in the experiments. The generality of ferroelasticity in halide perovskites stems from their soft bonding characteristics. This work shows the feasibility of using LHP twin domain walls as optical guides of internal photoexcitations, capable of nonvolatile on–off switching and tunable positioning endowed by their universal ferroelasticity. Abstract : Ferroelastic twin domain walls in lead halide perovskites are visualized using nonpolarized light and simple imaging configurations. These atomically thin domain walls become reflective at high angles and steer energy transport inside halide perovskites optically. Ferroelasticity is found to be universal across lead halide perovskite phases and families, originating from their soft bonding characteristics.